LCCB as a Professional Learning Community (PLC) in the Eyes of the Faculty - Cuelo, Randdie P. (JPAIR Multidisciplinary Research, 2011)
This study aimed to assess, through the perceptions of its faculty, the practices of La Consolacion College Bacolod (LCCB) relating to professional learning communities (PLC). Ninetytwo faculty responded to the 52-item standardized instrument "Professional Learning Community Assessment-Revised" developed by Dr. Diane Olivier of the University of Louisiana measured perceptions towards the practice of the six dimensions of PLC. Results revealed that teachers positively perceive and agree that LCCB is a professional learning community by virtue of the evident practices of the PLC dimensions. Of the six dimensions, 'collective learning and application' ranked first, while 'shared and supportive leadership' was ranked the lowest. The perceptions of the teachers significantly vary, indicating that teaching classification, teaching experience, and affiliation in the program has an influence on how a teacher recognizes various institutional practices. The more those teachers are involved in practices of the College, the more likely they are to impress positive perception. The study concluded that LCCB is a legitimate professional learning community from the eyes of its teachers and affirmed the finding of a previous related study that a shared and supportive leadership continues to be a need and demand by the faculty of the College.
Keywords: PLC; leadership; administration; organization